Harry E. Yarnell papers - Yarnell, Harry E. (Harry Ervin), 1875-1959.; Angwin, William A.
Correspondence, writings, notes, reports, printed matter, and other papers relating to conditions in East Asia before and during the renewal of hostilities between China and Japan in the late 1930s. Subjects include the evacuation of U.S. citizens from China, military operations of Japanese and Chinese troops, the Japanese blockade, and the situation at Jiujiang, Jiangxi Sheng, China (Kiukiang). Includes pamphlets and articles concerning the Far East in the 1930s, copies of the North-China Daily News (1937 August-November), and an unpublished article by William A. Angwin entitled "The China Incident" (1938) containing an account of the sinking of the gunboat Panay. Correspondents include William H. Allen, Frank H. Clark, Clarence E. Gauss, Nelson T. Johnson, J. Weldon Jones, William D. Leahy, Charles Little, and Frank P. Lockhart.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Allen, William H. -- 1874-1963 -- Correspondence; Clark, Frank H. -- Correspondence; Gauss, Clarence E. -- Correspondence; Johnson, Nelson T. -- 1887-1954 -- Correspondence; Jones, J. Weldon -- 1896- -- Correspondence; Leahy, William D. -- Correspondence; Little, Charles -- Correspondence; Lockhart, Frank P. -- Correspondence; United States. -- Navy. -- Asiatic Fleet; Panay (Gunboat); North-China daily news; Americans -- China; Chinese newspapers; Sino-Japanese War, 1937-1945.; China -- Foreign relations -- Japan; China -- History, Military -- 1912-1949.; East Asia -- History; Japan -- Foreign relations -- China; Japan -- History, Military -- 1868-1945.; Jiujiang (Jiangxi Sheng, China) -- History; Naval officers